LINGUISTIC AND CULTURAL CHARACTERISTICS OF ENGLISH AND UZBEK FAIRY TALES - Usmonova Sevara Sultanovna; Malikov Husniddin Sharobiddin o’g’li (Лучшие интеллектуальные исследования, 2024)
Abstract: This article analyzes the texts of Uzbek and English fairy tales, which make it possible to determine in the world's linguistic landscape how the language units of different ethnic groups associated with the perception and verbalization of fairy tales are formed in the human mind.